The political disenfranchisement of convict corruption - Prof Johan Jasin (Indonesia Prime, 2018)
The preamble to the Constitution of the Republic of Indonesia year 1945 the Government of Indonesia commissioned to build the nation and the country to realize the well-being Development that uses tax funds and foreign loans effectively and efficiently. But public officials often take advantage of opportunities to enrich themselves through corruption. The interior Ministry mentioned that between the years 2004 until 2012 there were cases of corruption involving regional chiefs and 277 of about 1,500: An official area as well as members of the legislature. But, among the corruption the, only a small part was fined for his political rights In the last four years, the majority was sentenced to the average corruption of light prison under four years, to give a systemic deterrent effect that was worth additional penalties such as political disenfranchisement. According to international human rights documents, corrupt political corruption is seen as a violation, but national legislation, therefore, legitimizes the existence of human rights restrictions to defend the rights of others, the nation and the state alone. Restricting human rights through corrupting political defranchising by attempts to make it a deterrent, simplifying the law enforcement process, saving the state money, as well as simplifying and simplifying the use of welfare development funds General